Earmarking of environmental taxes: efficient, after all - Jukka Pirttilä (Bank of Finland, 1998)
The paper analyses the benefits of earmarking the environmental tax revenues in a second-best world with asymmetry of information between government and taxpayers.Taxpayers are assumed to have taste differences over consumption of an environmentally harmful activity.The government, which cannot observe these preferences, pursues Pareto-efficient taxation involving compensation to the potential losers of tax policy.Within this framework, it is shown that earmarking environmental tax revenues on projects that are beneficial to the losers of the environmental policy may alleviate problems concerning asymmetric information and facilitate more efficient environmental policy.
URN:NBN:fi:bof-20140807241
Keywords: 330; Environmental taxation; earmarked taxes; Pareto-efficient taxation; second-best analysis